Influence of patient and provider factors on the workload of on-call physicians: A general internal medicine cohort observational study. Issue 35 (August 2016) - Hsu, Nin-Chieh; Huang, Chun-Che; Jerng, Jih-Shuin; Hsu, Chia-Hao; Yang, Ming-Chin; Chang, Ray-E; Ko, Wen-Je; Yu, Chong-Jen
Abstract : Abstract: Factors associated with the physician workload are scarcely reported. The study aims to investigate the associated factors of on-call physician workload based on a published conceptual framework. The study was conducted in a general internal medicine unit of National Taiwan University Hospital. On-call physician workloads were recorded on a shift basis from 1198 hospitalized patients between May 2010 and April 2011. The proxy of on-call workloads included night calls, bedside evaluation/management (E/M), and performing clinical procedures in a shift. Multivariable logistic and negative binomial regression models were used to determine the factors associated with the workloads of on-call physicians. During the study period, 378 (31.6%) of patients had night calls with related workloads. Multivariate analysis showed that the number of patients with unstable conditions in a shift (odds ratio [OR] 1.89 and 1.66, respectively) and the intensive care unit (ICU) training of the nurse leader (OR 2.87 and 3.08, respectively) resulted in higher likelihood of night calls to and bedside E/M visits by the on-call physician. However, ICU training of nurses (OR = 0.37, 95% confidence interval: 0.16–0.86) decreased the demand of performing clinical procedures by the on-call physician. Moreover, number of patients with unstable conditions (risk ratio [RR] 1.52 and 1.55, respectively) had significantly increased the number of night calls and bedside E/M by on-call physicians by around 50%. Nurses with N1 level (RR 2.16 and 2.71, respectively) were more likely to place night calls and facilitate bedside E/M by the on-call physician compared to nurses with N0 level. In addition, the nurse leaders with ICU training (RR 1.72 and 3.07, respectively) had significant increases in night calls and bedside E/M by the on-call physician compared to those without ICU training. On-call physician workload is associated with patient factors and the training of nurses. Number of unstable patients in a shift may be considered in predicting workload. The training of nurses may improve patient safety and decrease demand for clinical procedure.